2022
DOI: 10.2147/dhps.s325150
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Practice with Antibiotics and Its Associated Factors Among Community of Bule-Hora Town, South West Ethiopia

Abstract: Background Self-medication with antibiotics is being practiced worldwide with high prevalence, mostly in developing countries. Several factors induce the practice of self-medication, such as irrational and uncontrolled dispensing of medicinal substances, difficulty accessing health-care systems, and cost of diagnosis. Thus, this study assessed the prevalence of self-medication with antibiotics, and its associated factors among the community of Bule-Hora town, South West Ethiopia. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…A pre-test and structured questionnaire was employed to gather relevant data. Kassa et al, 2022 [ 30 ] The study employed a multi-stage sampling technique. Samples were selected using a lottery method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-test and structured questionnaire was employed to gather relevant data. Kassa et al, 2022 [ 30 ] The study employed a multi-stage sampling technique. Samples were selected using a lottery method.…”
Section: Resultsmentioning
confidence: 99%
“… 60.1% Common cold (32.6%), common febrile illness (28.7%), diarrhea (27.1%), malaria (3.7%). Kassa et al 2022 [ 30 ] Respiratory problems 29 40.3 Gastro intestinal problems 28 38.9 Skin problems 3 4.2 Urinary tract problems 6 8.3 Unidentified cases 6 8.3 Demissie et al 2022 [ 32 ] Aches and pains (15.5%) Typhoid and typhus (8.1%) Cough (6.3%) Community acquired Pneumonia (CAP) (3.4%) Diarrhea (4.3%) amebiasis (2.5%) Tonsillitis (1.7%) wound (1.5) Mossa et al 2012 [ 35 ] Headache 30(38.5) Fever 28(35.9) Cough 11(14.1) Diarrhea 8(10.2) Abdominal pain 8(10.2) Joint & back pain 28(35.9) Nausea & vomiting 6(8.5) Other 6(8.5)...…”
Section: Resultsmentioning
confidence: 99%
“…The self-reported reasons for choosing SM are varied and include insufficient time to consult with medical personnel, inability to schedule a quick appointment, long distances and travel times to reach the nearest hospitals and clinics, limited openings for immediate treatment from a hospital during busy hours, lack of healthcare services, and unaffordable consulting fees for medical doctors [ 16 ]. Studies conducted in Europe [ 17 ], South West Ethiopia [ 18 ], and Bangladesh [ 19 ] show that individuals choose SM for common ailments like fever, cold, acidity, abdominal pain, cough, headache, back pain, typhoid, typhus, cough, community-acquired pneumonia, diarrhea, amebiasis, tonsillitis, wounds, allergies, and diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating antibiotic access and use outside facilities in LMICs concluded that long waiting times in healthcare facilities, easy and unrestricted accessibility of drug retail outlets in communities, and a lower cost per treatment course dispensed were the main reasons for accessing antibiotics without prior formal consultation [16][17][18]. While largely overlooked in antimicrobial stewardship, antimicrobial dispensing and use outside healthcare facilities may contribute towards maintaining a high AMR burden [19][20][21].…”
Section: Introductionmentioning
confidence: 99%